The Linguistic Landscape of Urban Vellore: A Comprehensive Analysis of Language Distribution, Choice, and Implications in the Commercial Space Through Shop Signs - Mishra Sneha (Darnioji daugiakalbystė)
The current study explores the language distribution on commercial shop signs in the linguistic landscape (LL) of urban Vellore, a city in the Tamil Nadu state of India. The study aims to contribute to the understanding of the LL in urban Vellore by focusing on the analysis of shop signs in the commercial space. A previous survey of the linguistic situation of the region highlights the presence of several Indian and foreign languages in the verbal repertoire of the inhabitants, yet the visual representation of the shop signs render prominence to bilingual signs with English and Tamil occupying maximum space. The study utilizes the conceptual frameworks of Communication Accommodation Theory (CAT) and Social Representation Theory (SRT) to explore the dynamics of shop signs. The study analyzed the total of 250 shop signs from 5 sample areas and interviewed 25 sign producers and 15 sign readers to understand the motivation and implication of language choices on the name boards of shops. The study found that English enjoys the highest visibility and dominance among all languages, while Tamil is salient next to English on the shop signs. The shop owners’ language choices on shop names are driven by a desire to accommodate customers from different linguistic backgrounds, to project their cultural identity, and to align with the values of globalization and modernity. The study concludes that there is a dialectical relationship between the city and the inhabitants, as they develop and accommodate one another in response to the city along with its language policies, identity issues, and expectations. The LL of Vellore’s shop signs is a reflection of the cultural, linguistic, and economic landscape of the city, and provides a window into the complexities of language use in multilingual urban environments.